2012
DOI: 10.1007/s00464-012-2402-5
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve for endoscopic submucosal dissection in an established experimental setting

Abstract: Our study suggests that performing 30 ESD resections in an ex vivo simulator leads to a significant improvement in safety and efficiency of performing the ESD technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 26 publications
1
51
1
2
Order By: Relevance
“…Likewise, these techniques have shown better results than conventional ESD, especially in terms of safety, even when performed by an endoscopist with minimal experience in ESD (less than 50 real procedures). This is noteworthy, owing to the fact that in western countries as far as it is known, expertise in ESD is hardly ever achieved at the beginning of the learning period [2,13]. In a recent observational study [14], lack of counter traction guided by gravity has shown to be an independent predictive factor for difficult ESD, so it is develop of devices to help to overcome this drawback is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, these techniques have shown better results than conventional ESD, especially in terms of safety, even when performed by an endoscopist with minimal experience in ESD (less than 50 real procedures). This is noteworthy, owing to the fact that in western countries as far as it is known, expertise in ESD is hardly ever achieved at the beginning of the learning period [2,13]. In a recent observational study [14], lack of counter traction guided by gravity has shown to be an independent predictive factor for difficult ESD, so it is develop of devices to help to overcome this drawback is required.…”
Section: Discussionmentioning
confidence: 99%
“…No differences in terms of safety and efficacy were registered between the three approaches. Nevertheless, MG-ESD proved to be faster and more efficient than conventional ESD and water-jet assisted ESD (min per cm 2 10.85 vs. 7.43 vs.…”
Section: Introductionmentioning
confidence: 99%
“…95 In a study of 2 novice learners who each performed gastric ESD on 60 lesions each in an ex vivo porcine model, the total resection time, en bloc resection rate, and perforation rate all improved for both endoscopists when the last 30 resections were compared with the first 30 resections. 96 The authors calculated that the cost to train an endoscopist with 30 ex vivo gastric porcine procedures (assuming 6 lesions per stomach) would be US$8410, given the cost of the simulator used, the gastric specimens, and the disposable devices used. In comparison, the authors calculated that the cost to train an endoscopist with 30 in vivo gastric porcine procedures (also assuming 6 lesions per stomach) would be about US$16,000.…”
Section: Training Modelsmentioning
confidence: 99%
“…Os resultados foram expressos em porcentagem, ou seja, representam a proporção de cada compartimento (camadas que constituem a parede do estômago) presente no fragmento avaliado com relação ao fragmento total (espessura total). Essas variáveis foram definidas a partir da literatura médica atual que recomenda como critérios principais de proficiência da técnica a quase total ausência de complicações (sangramento, perfuração, morte do suíno), menor tempo de ressecção da lesão e alta taxa de ressecção em bloco, que foi representada pelo baixo número de peças fragmentadas durante a ressecção 41,42,47,[59][60][61][62][63] . As variáveis foram coletadas por um observador independente do estudo após cada ressecção, a primeira (D1), segunda (D2) e terceira (D3).…”
Section: Métodos -23unclassified
“…[41][42][43][44][45][46][47][48][49][59][60][61][62][63] . A primeira fase deste estudo, através da análise de tendência desses indicadores, mostra que da primeira até a terceira dissecção houve um tempo de ressecção mais rápido ao longo do aprendizado (p < 0,001) e um menor número de casos de sangramento, quando comparamos a primeira com a terceira dissecção (p = 0,047), o que não é diferente do que é relatado na literatura atual [44][45][46][47] . Além disso, houve uma melhora na percepção de segurança ou autoconfiança entre os participantes (p < 0,001).…”
Section: Análise De Curva Rocunclassified